Geomorphological analysis of the San Domino Island (Tremiti Islands, Southern Adriatic Sea). Results from the 2019 Geomorphological Field Camp of the MSc in Geological Science and Technology (University of Chieti-Pescara). Issue 3 (9th December 2020) - Buccolini, Marcello; Carabella, Cristiano; Paglia, Giorgio; Cecili, Alessandro; Chiarolanza, Gianluca; Cioria, Camilla; Conicella, Camilla; D'Alonzo, Antonio; De Viti, Laura; Di Carlo, Fedora; Di Francesco, Fausto; Di Luzio, Mattia; et al.
ABSTRACT: The 2019 Geomorphological Field Camp at San Domino Island (Tremiti Islands, Southern Adriatic Sea) is the result of geological and geomorphological field work activities carried out by a group of students attending the Geomorphological field mapping course of the Master's Degree in Geological Science and Technology (University of Chieti-Pescara). The main map (1:5000 scale) was obtained through an integrated approach that incorporates morphometric analysis, geological and geomorphological ﬁeld mapping, and geomorphological proﬁles drawing. Activities were carried out by all students, divided into six working groups of three to four persons each. The field camp and field work activities made it possible to produce a detailed thematic map, as a scientific tool to depict the San Domino Island landscape, and to outline some geomorphological issues in terms of possible constraints to landscape evolution, geomorphological processes distribution, and natural hazard assessment.